Dominant Weathering Profile Assessment of Kebo-Butak Volcanic Rocks in Gedangsari and Ngawen area, Yogyakarta, Indonesia - Fathan Hanifi Mada Mahendra; I Gde Budi Indrawan; sugeng sapto surjono (Journal of Applied Geology, 2021)
The Gedangsari and Ngawen area is predominantly composed of volcanic and volcaniclastic sequencesdistributed east – west direction of the northern parts of Southern Mountain. The massive tectonism as well as tropical climatein this region have been producing weathering profiles in varying thickness which inevitably affects thegeotechnical properties. This study aims to assess the dominant weathering profileof the lower part of Kebo-Butak Formation as well as evaluating the distribution of the discontinuity. In order to know the dominant weathering profile and discontinuity evaluation, this study utilizes a total of  26 panels from five stations investigated through a geotechnical data acquisition including the geological condition, weathering zones, joint distribution, and discontinuity characteristics. The result shows four types of dominant weathering profiles in lower part of Kebo-Butak Formation called as dominant weathering profile A, B, C, and D. Profile A, B, C consisted of a relatively identical weathering degree pattern of fresh, slightly, moderately, completely weathered zone with the variation of thicknesses. However, the weathering degree in profile D reached the residual soil degree controlled by more intensive joints. The fine-grained sedimentary rocks also tends to have smaller spacing, shorter persistence, and higher weathering degree of discontinuities as compared to coarse-grained sedimentary rocks.